ChemInform Abstract: Chiral Surfactant‐Type Catalyst for Asymmetric Reduction of Aliphatic Ketones in Water. Issue 16 (28th March 2013) - Li, Jiahong; Tang, Yuanfu; Wang, Qiwei; Li, Xuefeng; Cun, Linfeng; Zhang, Xiaomei; Zhu, Jin; Li, Liangchun; Deng, Jingen
Abstract The remarkable enantioselectivities are explained by synergistic effects between the metal center and the hydrophobic microenvironment in the metallomicelles.